Kemiskinan dan Pemberdayaan Masyarakat - Hendrikus Triwibawanto Gedeona (Centre for Public Policy and Management Studies, 2008)
Various development strategies have been applied to alleviate poverty. However, poverty remains a critical problem in Indonesia. Due to this problem, the most popular strategy is empowerment. This strategy not only aims at distributing aids to poor people but also tries to make them independently able to get out of the poverty trap. Empowerment based development strategy considered to be able to resolve the root of poverty.